The French Experience - Bougard, Marie-Therese. (London : BBC, 1994)
Viewers are shown how to talk about buying food, from baked goods, to vegetables, to cooked meats. In addition, viewers are introduced to the research center director at a major frozen foods company and to chocolate connoisseurs at the highly exclusive Club des Croqueurs de Chocolat, whose 150 members have assembled for their annual dinner.
DVD.
French dialogue; English subtitles.
Keywords: French language -- Conversation and phrase books -- English; French language